Pengaruh Mekanisme Tata Kelola Perusahaan Terhadap Penghindaran Pajak Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - rofiana adawiyah; Aloysius Harry Mukti; Triana Yuniati (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This study aims to test and analyze the effect of corporate governance mechanisms proxied by institutional ownership, the proportion of independent commissioners and the total audit committee on tax avoidance practices with company size as a moderating variable in infrastructure companies listed on IDX during the 2019-2022 period. The population in this study were infrastructure companies in the 2019-2022 period which resulted in 121 samples of Company financial statements. The results of this study indicate that institutional ownership, the total audit committee has a significant positive effect on tax avoidance, the proportion of the board of commissioners has a significant negative effect on tax avoidance, company size is unable to moderate institutional ownership, proportion of independent commissioners and total audit committee on tax avoidance.